Lean Analytics (Audio Book) - Croll, Alistair; Yoskovitz, Benjamin (O'Reilly Media, Incorporated, 2019)
Marc Andreesen once said that "markets that don't exist don't care how smart you are." Whether you're a startup founder trying to disrupt an industry, or an entrepreneur trying to provoke change from within, your biggest risk is building something nobody wants. Lean Analytics can help. By measuring and analyzing as you grow, you can validate whether a problem is real, find the right customers, and decide what to build, how to monetize it, and how to spread the word. Focusing on the One Metric That Matters to your business right now gives you the focus you need to move ahead-and the discipline to know when to change course. Written by Alistair Croll and Ben Yoskovitz, the book lays out practical, proven steps to take your startup from initial idea to product/market fit and beyond. Packed with over 30 case studies, and based on a year of interviews with over a hundred founders and investors, the book is an invaluable, practical guide for Lean Startup practitioners everywhere.
Online resource; Title from title page (viewed February 26, 2019)
Keywords: Audiobooks; Livres audio